Impact of cover cropping on arthropods in corn on the western high plains - Davis, Holly N. (Kansas State University, 2008)
This study evaluated whether using a cover crop with corn would increase the threat from spider mites in western Kansas because cover crops may serve as a winter host. This study also evaluated whether a cover crop could affect corn rootworm and other ground dwelling arthropods in the cornfield. In the first study, downy brome, Bromus tectorum L., was used as the winter cover crop. There were two trials repeated for three years each. Each trial included: two amounts of irrigation, downy brome, and herbicide to control weeds. In the first trial there were no significant differences in corn rootworm, Diabrotica virgifera LeConte, damage across treatments, because there were no differences in brome residue across the treatments. In the second trial, corn rootworm damage was significantly more in plots with higher amounts of downy brome residue. There were no differences in numbers of spider mites: Banks grass mites, Oligonychus pratensis (Banks) or twospotted spider mites, Tetranychus urticae Koch, across treatments. Spider mite populations appeared to be suppressed by the predatory mite Neoseiulus spp., which also overwintered in the cover crop. Corn rootworm samples taken from a no-till irrigation experiment were variable among irrigation treatments but indicated a trend for rootworm damage to increase with increasing irrigation. In the second study, winter wheat, Triticum aestivum L., was used as the winter cover crop. There were three trials repeated for three years each. Each trial included two amounts of irrigation and winter wheat and three amounts of herbicide to control weeds. Upon completion of the agronomy trials, the plots were split into two subplots and one was tilled. Pitfall traps were installed to capture ground dwelling arthropods: (Coleoptera: Carabidae), wolf spiders (Araneae: Lycosidae) and crickets (Orthoptera: Gryllidae). Four carabid genera were more common under no-till conditions. One was more common in tilled plots. Five carabid genera were more common in plots with a history of high weed densities. Two carabid genera were more numerous in plots with the history of a cover crop. Crickets were more common under no-till conditions. Wolf spiders were more common in no tillage with a history of a cover crop.
Keywords: cover crop; downy brome; Western corn rootworm; Predatory mites; Spider mites; Carabids; Agriculture, Agronomy (0285); Biology, Entomology (0353)